2019
DOI: 10.1021/acsomega.8b03205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of the Androgen Receptor DNA-Binding Domain Inhibitor Pyrvinium

Abstract: Pyrvinium was identified as the first small molecule inhibitor of the androgen receptor (AR) DNA-binding domain (DBD). It was also among the first small molecules shown to directly inhibit the activity of AR splice variants (ARVs), which has important clinical implications in the treatment of castration-resistant prostate cancer. Important questions about pyrvinium’s mechanism of action remain. Here, we demonstrate through mutational analysis that amino acids 609 and 612 are important for pyrvinium action. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…However, although PP decreased prostate weight and did not affect lean body mass, it also decreased bone mineral density [ 121 ]. Later studies showed that several splicing factors, such as DDX17, had reduced interactions with AR in the presence of pyrvinium [ 122 ]. However, pyrvinium did not alter the levels of AR-Vs in several PCa cell lines [ 121 , 122 ].…”
Section: Ar-targeting Strategies To Overcome Adt and Asi Resistancmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although PP decreased prostate weight and did not affect lean body mass, it also decreased bone mineral density [ 121 ]. Later studies showed that several splicing factors, such as DDX17, had reduced interactions with AR in the presence of pyrvinium [ 122 ]. However, pyrvinium did not alter the levels of AR-Vs in several PCa cell lines [ 121 , 122 ].…”
Section: Ar-targeting Strategies To Overcome Adt and Asi Resistancmentioning
confidence: 99%
“…Later studies showed that several splicing factors, such as DDX17, had reduced interactions with AR in the presence of pyrvinium [ 122 ]. However, pyrvinium did not alter the levels of AR-Vs in several PCa cell lines [ 121 , 122 ]. As a result, this drug, though promising, has not progressed to the stage of clinical investigation.…”
Section: Ar-targeting Strategies To Overcome Adt and Asi Resistancmentioning
confidence: 99%
“…In addition, only the ligand-binding domains (LBDs) of NRs were targeted in this study. However, it has been suggested that the DNA binding domains (DBDs) of NRs and even the DNA sites recognized by NRs can also be targeted by ligands (Brodie 2005 ; Meijsing et al 2009 ; Li et al 2014 ; Dalal et al 2014 ; Shizu et al 2018 ; Frank et al 2018 ; Pal et al 2019 ; Veras Ribeiro Filho et al 2019 ). Thus we expect that the application of our in silico method to these new molecular interfaces will also facilitate potential EDC prediction.…”
Section: Discussionmentioning
confidence: 99%
“… BiAb 3E10-AR441 Bispecific antibody complementary to aa 302-318 in NTD [ 109 ] . AR-DBD targeting: inhibits AR interaction with DNA Pyridium pamoate Interacts with AR-DBD already bound to DNA to prevent RNA pol II recruitment [ 110 , 111 ] . VPC compounds Binds region under DBD P-box reducing interactions with AR and chromatin [ 112 , 113 ] .…”
Section: New Aris To Combat the Resistance Mechanismsmentioning
confidence: 99%